Fundamental of Entrepreneurship (ENT300) : Zoomers futsal centre / Muhammad Qaiyyum Yahya … [et al.] - Yahya, Muhammad Qaiyyum; Ali Hassan, Mohd Imran; Abu Bakar, Mohd Ruzaini; Azeman, Ahmad Azri; Yusuf, Mohd Izwan; Shaffa'ee, Mohd Shazwan (2014)
A business plan is a formal statement of a set of busmess goals, the reasons why they are believed attainable, and the plan for reaching those goals. It may also contains background Information about the organization or team attempting to reach this goals. A business plan is very important in an organization in order to have effective and efficient controls over the flow of the business organization. Busmess plan is also known as a working paper, business proposal, project paper or prospectus.